1970
DOI: 10.3126/on.v9i1.5739
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of some Petal Extracts against Xanthomonas campestris pv. campestris

Abstract: The aqueous petal-extracts of 20 plants were screened by agar diffusion methods for their antibacterial activity against Xanthomonas campestris pv. campestris, a causal organism of black rot of cabbage and cauliflower. X. campestris pv. campestris was found most sensitive to the petal extracts of Tagetes erecta and Chrysanthemum coronarium. Some of the other plants such as Acacia fernesiana, Anthocephalus cadamba, Bombax malabaricum, Lathyrus odoratus, Rosa damascena and Thevetia nerifolia also showed the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Due to this, research focused on compounds derived from natural sources such as plant extracts and ible application in agriculture is being intensified. Many natural products, including plant extracts, have been shown to possess marked inhibitory activity against a variety of pathogens ., 2000 ;Benkeblia, 2004;Bhai et al, 2005;Bajpai et al, 2008;Paret Ranaware et al, 2010;Zhao et al, 2011;Tiwari and Das, 2011;Bhardwaj et al, 2011;De Britto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, research focused on compounds derived from natural sources such as plant extracts and ible application in agriculture is being intensified. Many natural products, including plant extracts, have been shown to possess marked inhibitory activity against a variety of pathogens ., 2000 ;Benkeblia, 2004;Bhai et al, 2005;Bajpai et al, 2008;Paret Ranaware et al, 2010;Zhao et al, 2011;Tiwari and Das, 2011;Bhardwaj et al, 2011;De Britto 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the bacteriostatic activity of 20 kinds of botanical extracts also showed that the leaf extracts of Acacia arabicae , Acacia fernesiana , Acacia catechu , Achyranthus asper , Aegle marmelos , Asparagus racemosus , A. indica , Callistemon lanceolatus , and Camellia sinensis showed an inhibitory effect against Xcc ( Bhardwaj and Laura, 2009 ). Xcc was also kill by the petal extracts of T. erecta , Chrysanthemum coronarium , A. fernesiana , Anthocephalus cadamba , Bombax malabaricum , Lathyrus odoratus , Rosa damascena , and Thevetia nerifolia ( Bhardwaj and Bhardwaj, 2011 ). These studies indicated that the anti -Xcc activity was not only related to the plant material, but also to the plant parts.…”
Section: Biological Control Of Xanthomonas Campestris ...mentioning
confidence: 99%
“…A large number of crop extracts from Acacia , Tylophora , Ocimum , and other genera have been reported to show a controlling effect on Xcc ( Tiwari et al, 2004 ; Sain, 2007 ; Bhardwaj and Laura, 2009 ; Kumar et al, 2018 ; Fontana et al, 2021 ; Table 1 ). Moreover, the antimicrobial activities of extracts from different parts of the same plant are also different ( Bhardwaj and Laura, 2009 ; Bhardwaj and Bhardwaj, 2011 ; Table 4 ). The components of these plant extracts are complex; therefore, it is difficult to determine the exact substances or particular components of a class of substances that exert the antibacterial activities of the extracts.…”
Section: Future Workmentioning
confidence: 99%
“…(2011) [5] Evaluated some petal extracts against Xanthomonas campestris pv. campestris and stated that extract of Latharus odoratus was significantly effective against Xanthomonas campestris pv.…”
Section: B Pathogenic Ability Of Xanthomonas Citri Subsp Citri On Acid Lime Leavesmentioning
confidence: 99%